Presentation to the book - Kanninen, M.; Pedroni, L.; Robledo, C. (Center for International Forestry Research, 2005)
This chapter provides brief information on the background and aim of the workshop, the participants and the division of the workshop sessions. The last part is information on the three main parts of the content of the book.